The wisdom of failure : how to learn the tough leadership lessons without paying the price - Weinzimmer, Laurence G. (Jossey-Bass, 2013)
The "how-not-to" leadership book. There is a paradox in leadership: we can only succeed by knowing failure. Every accomplished leader knows there are minefields of failures that need to be navigated in order to succeed. Wouldn't it be great to have the insights to help you prevent from making avoidable mistakes? Unfortunately, in business talking about mistakes can be taboo, and, at a certain level, learning from failure is not an option. Weinzimmer and McConoughey speak frankly about the things that are difficult to talk about- the unvarnished truths necessary to become a successful leader. Based on a groundbreaking 7-year study of what almost 1000 managers across 21 industries really think about lessons from failures. Includes exclusive interview material from CEOs at a wide range of organizations, including major firms such as Caterpillar, Priceline.com, and Allstate; startups; and entrepreneurial small businesses. Drills down into failure to uncover the strategies that aspiring leaders need in order to avoid the most damning leadership mistakes: unbalanced orchestration, drama management, and reckless vanity. Learning from the mistakes of others is a necessary part of the journey of effective leadership, and this book offers an indispensable guide to learning these powerful lessons-without paying the price of failure.